Alcohol Consumption in Patients with Psoriasis and its Relationship to Disease Severity - Vasili, Ermira; Borici, Sidita; Alia, Erisa; Cano, Elna; Kuneshka, Loreta; Hoxha, Iris (Journal of Nutritional Therapeutics, 2013)
Moderate to severe psoriasis is associated with increased alcohol intake and excessive mortality from alcohol-related causes. Alcohol biomarkers are those providing an objective measurement of its consumption. The objective of this study is to assess alcohol consumption in a cohort of patients with psoriasis and to investigate the influence of alcohol intake on disease severity. Patients with psoriasis hospitalized at the Clinic of Dermatology, in Mother Teresa University Hospital were recruited in this cross- sectional study. Alcohol consumption was assessed via CAGE questionnaire and the self- reported amount of alcohol consumed, whereas disease severity was evaluated via PASI scoring system. Blood specimens were taken at admission and levels of gamma glutamyltransferase (GGT), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and mean corpuscular volume of erythrocytes (MCV) were measured. Statistical analysis was performed using SPSS 20.0 statistical package. A total of 62 in- patients completed the study. Significant correlations were observed between GGT and AST values with raki and beer consumption, ALT value with raki, beer and wine consumption and MCV value with raki consumption. Disease severity did not correlate significantly with raki and beer consumption (p> 0.05). Logistic regression analysis between Psoriasis Area and Severity Index (PASI) score and raki consumption in male patients with psoriasis duration of more than 3 years resulted in statistical significance (b= 23.5, p< 0.05). Combination of parameters related to chronic alcohol consumption offers advantage over every isolated test. Measurement of simple laboratory parameters combined with self- report methods of consumption allows identification of users.